CURRENT STATE OF STANDARDIZATION IN THE FIELD OF METROLOGICAL SUPPORT OF INFORMATION AND MEASUREMENT SYSTEMS (Conferencea, 2024)
The article provides an in-depth analysis of the requirements of existing national and international standards for the metrological support of information and measurement systems. In particular, the results of a comparative analysis between GOST R 8.596-2002 and the first draft of its initial edition are presented. These standards encompass the fundamental rules and recommendations aimed at ensuring measurement accuracy, reliability, and metrological consistency within the system.